El Efecto Del Franquismo En La Representación De La Mujer En La Literatura Española. - DeAngelis, Julie E. (Tufts Archival Research Center, 2014)
Abstract: This thesis examines the effect of the Franco dictatorship on the representation of women in women's literature, focusing on the works of Carmen Martín Gaite.